THREE CHARACTER BUILDING BY USING COMIK WAYANG - Edi Sunjayanto Masykuri (UM Purworejo, 2016)
In this period of AEC, some countries in Asia have to compete each other in many aspects such as; economy, education, professionalism and so on. Indonesia should be ready to participate in. The educationhas to create qualified student, actually in character building because self-character of student is still degraded. The big question of it is how, what and when? Here, I will answer the problem; what is able to increase self-character of student and when is it done? The answer is we can use media creative and we can apply it from earlier student that is elementary school. Comic appears student’s imagination where optimize the right brain by visualization (text, picture and color). In addition, I use electronic comic and combine with Traditional Javanese story based on wayang.The research is to find the new perspective of creative media and student’s imagination by basic research, or to answer other questions practically by applied research. It is to show the effectiveness, student’s response and evaluation of the developed creative comic.